2011
DOI: 10.1590/s1677-04202011000300002
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and other biochemical defense responses of Macrotyloma uniflorum (Lam.) Verdc. (Horse gram) induced by high temperature and salt stress

Abstract: High temperature and salinity are the major ecological factors challenging crop productivity in the arid and semiarid regions of the world. Effects of high temperature (43-45°C) and salt stress (0.6 M) on Macrotyloma uniflorum (Lam.) Verdc. (Horse gram), were evaluated in terms of antioxidants and antioxidant enzymes. Both treatments caused typical stress responses in this tropical leguminosae. Oxidative stress indicators such as H 2 O 2 , TBARS, and proline were significantly elevated. Similarly, the antioxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
6
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 56 publications
4
6
0
3
Order By: Relevance
“…Hope' was higher than in 'CG3' at all temperatures (Figure 4). Similar to the findings of the current study, proline accumulation is more often observed in stress-tolerant plants than in sensitive ones (Chaitanya et al, 2001;Kumar et al, 2011;Naji and Devaraj, 2011). The proline content of cultivars, especially in 'R.…”
Section: Discussionsupporting
confidence: 90%
“…Hope' was higher than in 'CG3' at all temperatures (Figure 4). Similar to the findings of the current study, proline accumulation is more often observed in stress-tolerant plants than in sensitive ones (Chaitanya et al, 2001;Kumar et al, 2011;Naji and Devaraj, 2011). The proline content of cultivars, especially in 'R.…”
Section: Discussionsupporting
confidence: 90%
“…(Hassanein et al, 2012). These results are similar to Naji and Devaraj (2011) who found that peroxidase isozyme activity in horse gram increase under heat and salt stresses. T15= T3+T9 T21= T1+T3+T9 T27= T1+T2+T9 T4 = T1+T3 T10= Proline amino acid T16= T3+T10 T22= T1+T3+T8 T28= T1+T2+T10 T5 = T1 +T2 T11= T1+T8 T17= T2+T8 T23= T3+T2+T9 T29= T2+T9+T8 T6= T2+T3 T12= T1+T9 T18= T2+T9 T24= T3+T2+T10 T30= 100 % NPK…”
Section: Characters Treatmentssupporting
confidence: 89%
“…This indicated that the production of ROS is a major factor related to heat injury in maize plants. High temperature-induced oxidative stress enhanced the production of MDA contents has already been reported in wheat and horse gram (Savicka and Š kute 2010;Naji and Devaraj 2011). When plants are exposed to abiotic stress, membrane integrity is greatly hampered (Bajji et al 2002).…”
Section: Discussionmentioning
confidence: 87%